PENGARUH KUALITAS PRODUK, DISKON FLASH SALE DAN PERSEPSI RISIKO TERHADAP KEPUASAN PELANGGAN PRODUK THRIFT DI EVENT SOLO MARKETFEST - Eva Septiana; Heni Susilowati (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
Thrifting is the activity of buying second hand products wichs is becoming a trend for teenagers, young people, and even older people. The aim of the research is to determine the influence of product quality, flash sale discounts and risk perception on customer satisfaction with thrift products at the Solo Marketfest event. The population is consumers who buy thrift products at the Solo Marketfest event. The sampling technique using accidental sampling obtained 75 respondents. The questionnaire was distributed with the help of a Google form which was distributed to all customers who purchased thrift products at the Solo Marketfest event, measured on a 1-5 Liker scale. The collected data was processed using Multiple Linear Regression. The research results show that partially product quality and flash sale discounts do not influence customer satisfaction with thrift products at the Solo Marketfest event, however perceived risk is proven to influence customer satisfaction with thrift products at the Solo Marketfest event.